KOMERSIALISASI PENDIDIKAN (KAJIAN TEORITIS-FILOSOFIS PARADIGMA PENDIDIKAN NASIONAL KONTEMPORER) - Kadi ' (LPPM Institut Agama Islam Al-Hikmah Tuban, 2012)
The dynamics and the development of thinking about the world of education eventually led them to a collective consciousness about the rights they have, including the right to take an active role in managing education. Such awareness led movement pattern of relations between the community and the government in the management of education. New patterns arising from this shift that caused the tug in determining educational paradigms that are considered most suitable for the culture and dynamics of Indonesian society. Implementation of decentralization or privatization system (commercialization) education is a difficult choice but it should be done. Two choices have consequences respectively. With a mature mental readiness, cultural throwing responsibility which often occurs, can be avoided or at least minimized in such a way. the spirit of all the options is to increase community participation is widely and independently. Society apart should be made aware of their responsibilities on education should also be given the opportunity to be creative as possible in accordance with the position and the ability of each. The process of raising awareness and providing opportunities for the public to walk in balance without ignoring one of the two. Ignoring the process will only bear awareness education without meaning